THE EFFECTIVENESS OF PICTURE SERIES AND GRAPHIC ORGANIZER ON STUDENTS WITH HIGH AND LOW MOTIVATION IN COMPREHENDING NARRATIVE TEXTS - Indriati, Anie; Rukmini, Dwi (Language Circle: Journal of Language and Literature, 2016)
This study investigates whether picture series can be used effectively on high and low motivated students in comprehending narrative texts, how students who were trained by picture series differ significantly from those who were trained by GO, and whether there is an interaction among strategy, motivation, and reading achievement. The subjects of the study were the tenth grader of SMA Negeri 1 Salem in the Academic Year 2014/2015. Two of fourclasses were selected as the sample of the research.The experiment was set up according to a pre-test and post-test for both groups. The writer used an experimental research with factorial design 2 x 2 by technique of multifactor analysis of variance (ANOVA).The findings of this study indicate picture series is more effective than the GO. It can be seen from the results of the scores of the post test in experimental groupwere significantly different comparing to the post test scores in the control one.In addition, They regarded it very helpful for them of developing their reading skill. A good commitment and careful implementation that fulfill the requirements suggested in picture series influence on the success of the teaching reading comprehension of narrative texts.Â